HORNBILL: A First-in-Human Phase I/IIa Study of the Safety, Tolerability, and Early Pharmacodynamics of BI 764524 for Diabetic Macular Ischemia - Quan Dong Nguyen, MD, MSc; Chirag Jhaveri, MD; Maged Habib, MD; Yasir J. Sepah, MBBS; Khaled Nassar, MD, PhD; Bartlomiej Krawczyk, PhD; Gudrun Simons, PhD; Andrea Giani, MD; Elizabeth Pearce, PhD; Martin Gliem, MD; Mohamed Ahmed, MBBCh, MD; Sobha Sivaprasad, DM (Ophthalmology Science)
Objective: To report safety and early pharmacodynamic results from a first-in-human trial of intravitreal (IVT) anti-semaphorin 3A antibody in participants with diabetic macular ischemia (DMI). Design: HORNBILL, a phase I/IIa study of BI 764524, comprised a nonrandomized, open-label, uncontrolled, single-rising-dose (SRD) and masked, randomized, sham-controlled, multiple-dose (MD) parts. Participants: Adults with DMI and stable diabetic retinopathy (DR) treated with pan-retinal photocoagulation and without center-involving diabetic macular edema. Methods: Twelve participants received single IVT doses of BI 764524 0.5 mg (n = 3), 1.0 mg (n = 3), or 2.5 mg (n = 6) in the SRD part. Thirty-one participants received 3 IVT doses of BI 764524 2.5 mg (n = 21) or sham procedures (n = 10) at 4-week intervals and were followed to week 22 in the MD part. Main Outcome Measures: The primary SRD end point was the number of participants with dose-limiting events; secondary end points assessed drug-related and ocular adverse events (AEs). The primary MD end point was the number of participants with drug-related AEs; secondary end points included changes from baseline in foveal avascular zone (FAZ) area, best-corrected visual acuity (BCVA), and central subfield thickness (CST). Results: No dose-limiting events or drug-related AEs were reported with SRD; the highest tested dose (2.5 mg) was selected for the MD part. In the MD part, 2 investigator-assessed drug-related AEs (vitreous floaters and increased gamma-glutamyl transferase) were reported. No intraocular inflammation or occlusive retinal vasculitis cases occurred. At week 12 (4 weeks after the final injection), the adjusted mean FAZ area change was −0.004 mm2 in the BI 764524 group and +0.019 mm2 with sham. At week 22 (14 weeks after the final injection), the adjusted mean FAZ area change was −0.001 mm2 in the BI 764524 group and +0.010 mm2 with sham. No relevant BCVA and CST changes occurred. Conclusions: HORNBILL met the primary safety end points; all evaluated BI 764524 doses were well tolerated. These findings support further investigation of BI 764524 in participants with DR and retinal nonperfusion. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.